2006
DOI: 10.1248/bpb.29.1022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetic Study of Arsenic Trioxide in an Acute Promyelocytic Leukemia (APL) Patient: Speciation of Arsenic Metabolites in Serum and Urine

Abstract: Acute promyelocytic leukemia (APL) is characterized M3 in the French-American and British (FAB) classification and represents approximately 5-10% of all leukemia in adults. 1) In about 95-98% of the cases, APL is associated with the reciprocal translocation, t(15; 17)(q22; q21) 2,3) and the reciprocal fusion of the retinoic acid receptor (RAR)a gene on chromosome 17 with the promyelocytic leukemia (PML) gene on chromosome 15. The resulting PML-RARa fusion gene encodes a chimeric protein 4,5) that causes the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
5
38
1
2
Order By: Relevance
“…In fact, ATO has usually been infused either in the dose of 0.16 mg/ kg (or 10 mg/day) in 250-500 ml of normal glucose saline solution over 2-3 h once a day in Chinese studies [6,10,141], or in the FDA-approved dose of 0.15 mg/kg in 100-250 ml of 5% dextrose in either water or 0.9% sodium chloride solution over 1-2 h daily [8,9,142]. In addition, a reduced dose of 0.08 mg/kg/day (low dosage) corresponding to a 50% of the conventional dosage (0.16 mg/kg/day), has also been applied in the treatment of APL patients [143,144]. It should be noted that in two clinical trials, treating APL patients with a low dose of ATO yielded a similar complete remission rate (80%) compared to that (85.1%) attained with a conventional dosage [143,145].…”
Section: Administration Route and Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, ATO has usually been infused either in the dose of 0.16 mg/ kg (or 10 mg/day) in 250-500 ml of normal glucose saline solution over 2-3 h once a day in Chinese studies [6,10,141], or in the FDA-approved dose of 0.15 mg/kg in 100-250 ml of 5% dextrose in either water or 0.9% sodium chloride solution over 1-2 h daily [8,9,142]. In addition, a reduced dose of 0.08 mg/kg/day (low dosage) corresponding to a 50% of the conventional dosage (0.16 mg/kg/day), has also been applied in the treatment of APL patients [143,144]. It should be noted that in two clinical trials, treating APL patients with a low dose of ATO yielded a similar complete remission rate (80%) compared to that (85.1%) attained with a conventional dosage [143,145].…”
Section: Administration Route and Distributionmentioning
confidence: 99%
“…The pharmacokinetic studies in APL patients have been well discussed by using urine samples [6,144,169,176]. It has been demonstrated that urinary arsenic contents slightly increased during drug administration, and the total amounts of arsenic excreted daily into the urine accounting for approximately 1-8% of the daily dose [6].…”
Section: Metabolism and Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elle offre la meilleure résolution et les temps d'analyse les plus courts. De plus, cette technique peut être facilement appliquée à l'analyse de poudres suspectes, mais également à d'autres milieux biologiques comme le plasma ou le sang [2,29], ou à des matrices alternatives, cheveux ou ongles [30][31][32][33].…”
Section: Discussionunclassified
“…Nous avons au cours des dernières années été confrontés à plusieurs cas d'intoxication par l'anhydride arsénieux dans un cadre judiciaire (homicides, tentatives d'empoisonnement) ou médical (suicide). Depuis peu, l'arsenic est à nouveau prescrit en thé-rapeutique, ainsi l'anhydride arsénieux est employé dans le traitement de la leucémie aiguë promyélocytaire [2]. Parmi les sources alimentaires, citons les produits de la mer, riches en dérivés organiques non toxiques, arsénobétaïne (AB) en particulier, mais surtout l'eau de boisson pouvant contenir de l'arsenic inorganique toxique.…”
Section: Introductionunclassified